Intestinal parasites in ruminants from Gabtoli cattle market and Keraniganj, Dhaka - Akhter, Halima; Musa, Sharmin; Mukutmoni, Mandira; Barua, Priyanka; Khanum, Hamida (Bangladesh Journal of Zoology, 2022)
The present study was designed to determine the prevalence of intestinal parasites in ruminants. A total of 124 fecal samples from ruminants (92 samples from large ruminants – cattle, buffalo and 32 from small ruminants- goat and sheep) were collected from Gabtoli cattle market and Keraniganj, Dhaka from May to September 2017. Formol ether concentration technique was used to process the fecal samples. Among the large ruminants, the maximum prevalence was shown by Entamoeba sp. among protozoan parasites in Gabtoli (46.43%; CPG, 16.2±4.5) and Keraniganj (44.44%; CPG, 10.1±1.5) respectively. Fasciola sp. showed the uppermost prevalence (35.71%; EPG 173.6±61) in Gabtoli while, from Keraniganj, Dicrocoelium sp. (27.78%; EPG 6.4±2) showed the uppermost prevalence among the trematodes infesting large ruminants. Dipylidium sp. (35.71%; EPG 5.5±2.5) and Taenia sp. (35.71%; EPG, 13.1±1.5) showed high prevalence in Gabtoli cattle market, whereas, Keraniganj, the most prevalent cestode was Moniezia sp. (38.9%; EPG, 9±1). In both Gabtoli and Keraniganj, Ascaris sp. showed the highest prevalence (42.86%; EPG, 36.3±12 and 38.9%; EPG, 12.1±1, respectively) among the large ruminants. Among the small ruminants, the maximum prevalence was presented by Balantidium sp. (25%; CPG, 32.5±9.5) and Entamoeba sp. (25%; CPG, 30±1.5), Fasciola sp. (37.5%; EPG, 22.5±9.5), Taenia sp. (25%; EPG, 12.5±1) and Ascaris sp. (43.75%; EPG, 20±2), respectively, for protozoans, trematodes, cestodes and nematodes. Female ruminants showed higher prevalence of parasites than that in male. Bangladesh J. Zool. 49 (3): 423-434, 2021